OPTIMAL UTILIZATION OF TIMBER POLES AS STRUCTURAL MEMBERS OF FORMWORK - Lwambuka, Ladislaus (Tanzania Journal of Engineering and Technology, 2018)
Timber poles of the type "Mirunda" are commonly used in East Africa as formwork support structures for casting of reinforced concrete slabs, beams and canopies. It is also widely known that the "Mirunda" poles as structural members of formwork are massively used without any structural consideration and guidance. This common practice has resulted into wastage of natural resources and escalated construction costs. This study has attempted to establish the load bearing capacity of randomly selected "Mirunda" poles through laboratory testing. Using an existing construction site as a case study, the results have been used to establish the actual number of timber poles required to support freshly cast reinforced concrete slabs, beams and canopies. The loading has been assumed for normal accessibility as per specifications in BS 6399: Part1 (1984).with a dynamic factor arising from the impact of dropping the concrete onto the formwork as well as the dynamic effect of the concrete vibrating machine. A comparison has been made between the actual requirement and the quantity of timber poles counted on site. On basis of the study findings appropriate recommendations have been provided on how "Mirunda" poles can be optimally utilized as structural members of formwork.